International journal of game-based learning - IGI eBooks; IGI Global; Information Resources Management Association (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA), 2011)
This journal is devoted to the theoretical and empirical understanding of game-based learning. To achieve this aim, the journal publishes theoretical manuscripts, empirical studies, and literature reviews. The journal publishes this multidisciplinary research from fields that explore the cognitive and psychological aspects that underpin successful educational video games. The target audience of the journal is composed of professionals and researchers working in the fields of educational games development, e-learning, technology-enhanced education, multimedia, educational psychology, and information technology. IJGBL promotes an in-depth understanding of the multiple factors and challenges inherent to the design and integration of Game-Based Learning environments.
"An official publication of the Information Resources Management Association".
DBLP
Google Scholar
MediaFinder
Standard periodical directory
Ulrich's periodicals directory
Keywords: Educational games -- Periodicals; Computer-assisted instruction -- Periodicals; Adaptive games design; People with disabilities; Educational video games; Learning management systems; Game design; Instructional design; Video games in the classroom; Intelligent tutoring systems; Designing and developing video games; Learning styles; Mobile development; Augmented reality; Motivation; Emotions in educational video games; Role of instructors; Virtual worlds; Game-based learning; Electronic books